Rapid production of willow biomass using a novel microcutting-based field planting technology - Frenette-Dussault, Cédric; Benoist, Patrick; Kadri, Hafssa; Pitre, Frédéric E.; Labrecque, Michel (Ecological engineering, 2019)
•Microcuttings are a novel planting technology to establish willow plantations.•Microcuttings can produce high amounts of aboveground biomass in a short time.•Microcutting density and diversity did not influence aboveground biomass yields.•Microcutting plantations could deliver phytoremediation at lower costs. Phytoremediation is becoming recognised as a promising environmental approach to decontaminate land. However, establishing large-scale plantations for phytoremediation purposes can bear prohibitive costs. In order to deliver large-scale phytoremediation projects, easily implemented plant establishment solutions need to be available to practitioners. Here, we present a novel planting technology based on willow microcuttings for the rapid establishment of phytoremediation plantations. An experiment was performed testing the effect of microcutting planting density and diversity on various growth parameters including aboveground biomass yields. After two growing seasons, aboveground dry biomass reached an equivalent of 23.1 t/ha. Willow microcutting planting density and diversity did not significantly affect biomass yields, although other growth parameters (survival, stand density and mean stem height) differed across treatments. Our results suggest that this willow microcutting planting technology is viable at large-scale, robust across willow species and represents a lower cost alternative to more traditional planting technologies.